PERCEPTION OF BODY IMAGE RELATED TO LIVE WITH IMC WOMEN PHYSICALLY (Fiep Bulletin - online, 2016)
Body image can be conceptualized as a multidimensional construct that represents how individuals think, feel and behave about their physical attributes. Objective: To relate the degree of satisfaction with body image of women engaged in physical activity to their BMI. Methods: To check the current and ideal body image proposed by Stunkardet al scale was used. Measurements of weight and height were obtained in a single take, according recommended by the World Health Organization (WHO) standards. Conclusion: The majority of the individuals present themselves dissatisfied with their body image of themselves they do, considering the aesthetic distant goal. Overweight individuals are dissatisfied with their body image, however the relevant factor in this study was the realization that individuals within their ideal weight are also dissatisfied with their body image, leading us to see that the aesthetic standard is more important than the health standard.
Keywords: body image; IMC; physical activity.